“Didn’t Have to Melt My Eyeballs”: Student Responses to Learning by Podcast in Journalism Education - Bird, Dylan; Lim, Louisa; Aayeshah, Wajeehah; Zhao, Niles (Journal of University Teaching and Learning Practice, 2026)
This article uses a case study to explore how undergraduate students in a journalism class engaged with an educator-produced podcast as a pedagogical tool for asynchronous learning replacing out-of-class readings, and the podcast’s effectiveness in improving student learning outcomes. It highlights how both podcast production elements and curriculum design were considered to help refresh a journalism subject and engage students more deeply in their learning. A student survey revealed a strong preference for learning via podcast than other media, and that the podcast was both enjoyable and useful for their learning. End of semester results also provided strong evidence for the podcast’s effectiveness in enabling positive learning outcomes. The study delivers new insights into what key factors make podcasting an effective pedagogical tool in university education and illustrates the benefits of educators tailoring teaching resources to students’ media consumption habits.